Phytoplankton ecology in the Bay of Quinte, Lake Ontario: Spatial distribution, dynamics and heterogeneity. Issue 2 (3rd April 2018) - Munawar, M.; Fitzpatrick, M.; Niblock, H.; Kling, H.; Lorimer, J.; Rozon, R.
Abstract : The Bay of Quinte, a large riverine embayment located on the northeastern shores of Lake Ontario, has a long history of cultural eutrophication. While the Bay has been the subject of an extensive research and monitoring program that began in 1972, phytoplankton assessments have been limited to 2–3 index stations with few exceptions. Our study consisted of three separate surveys conducted during the summer of 2010 (June, August, September) at 12 sites spread evenly throughout the Bay. Among the major findings were that conditions in the Bay ranged from oligo- to mesotrophic in June, but were primarily eutrophic in August and September with algal blooms observed at 50–75% of the sites; the spatial extent limited only by incursions of oligotrophic water from Lake Ontario. Furthermore, primary productivity in the Bay (e.g. 43.3–109.6 mg C m −3 h −1 in September) was among the highest reported in the Great Lakes, indicative of a phytoplankton community very well adapted to its environment. We also found that the Bay of Quinte supported a diverse algal flora containing 140 unique species in June, 209 in August and 169 in September which we attribute to the variable physical environment. Of the 35 phytoplankton samples assessed, Diatomeae were the most prevalent taxa in 16 of those assemblages followed by Cyanophyta (including many toxigenic species) in 12. The relative importance of diatoms are often overlooked in studies of eutrophication yet two species in particular, Aulacoseira granulata and A. ambigua, were major contributors to both the algal standing crop and the elevated rates of primary production. We recommend that future research be directed at understanding the ecology, physiology and dynamics of these filamentous diatoms as well as their associations with filamentous and colonial cyanobacteria.